Membangun Kreativitas Literer melalui Pendampingan Penulisan Buku Antologi Siswa di SPM Madrasah Ulya PP. Miftahul Mubtadiin Krempyang Nganjuk - Yusuf, M.; Muda'i, Syaiful; Miftahuddin, Abd. Hafidz; Qurotul Aini, Siti Maryam; Rohmah, Nur Rulifatur (Universitas Pangeran Diponegoro Nganjuk, 2025)
This community service activity aims to develop the literary creativity of students at SPM Madrasah Ulya PP. Miftahul Mubtadiin Krempyang Nganjuk through the mentoring of anthology writing. The mentoring was conducted by a team of lecturers from various disciplines over six months, including writing training, workshops, and critique sessions. During the activity, students received materials on the basics of creative writing, narrative techniques, character creation, and story structure. The workshops featured professional writers and editors who shared their experiences and provided valuable additional materials. The critique sessions allowed students to present their work and receive constructive feedback from lecturers and peers. The results showed a significant improvement in students' writing skills, as evidenced by more structured writing, better language use, and deeper story development. Additionally, students' interest in writing and appreciation for literacy increased, as seen in more active class discussions, enthusiasm in participating in literacy activities, and improving the quality of their work. This program successfully sparked literacy and creativity among students.